Europe and the politics of capabilities - Salais, Robert; Villeneuve, Robert, 1943- (Cambridge ; New York : Cambridge University Press, 2004)
"This book demonstrates how an employment-oriented social policy in Europe can develop from a new, different set of policy principles, specifically 'a capability approach'. Taking inspiration from the work of Amartya Sen, this book focuses on the effective freedom people need to achieve their goals in life and work. The result of ongoing collaboration between researchers and social actors, it will appeal to social scientists, students, policy makers and all those concerned with the building of Europe."--Jacket
Preface / Odile Quintin -- 1. Introduction : Europe and the politics of capabilities / Robert Salais and Robert Villeneuve -- 2. Europe tested through its products : the Renault-Vilvoorde affair and its implication for industry and employment policies / Claude Didry -- 3. Competences-oriented logics and the politics of unemployability / Benedicte Zimmermann -- 4. Regional capabilities and the European employment strategy / Martin Heidenreich -- 5. The territorial pacts in Italy : the competitive corporatism assumption in question / Serafino Negrelli -- 6. Mobilising local capabilities for a European economic project : the case of Marseilles / Pierre-Paul Zalio.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Manpower policy -- European Union countries; Quality of work life -- European Union countries; European Union countries -- Economic policy; European Union countries -- Social policy; Regional planning -- European Union countries; European Economic Community countries -- Economic policy; European Economic Community countries -- Social policy; Emploi -- Politique gouvernementale -- Pays de l'Union européenne.; Qualité de la vie au travail -- Pays de l'Union européenne.; Pays de l'Union européenne -- Politique économique.; Pays de l'Union européenne -- Politique sociale; Aménagement du territoire -- Pays de l'Union européenne.; BUSINESS & ECONOMICS -- Labor; Economic policy; Manpower policy; Quality of work life; Regional planning; Social policy; European Union countries; Sozialpolitik; Wirtschaftspolitik; Regionalplanung; Arbeitspolitik; Planification régionale.; Politique de l'emploi.; Politique économique.; Politique sociale; Qualité de vie au travail; Pays de l'Union européenne.; Europäische Union; Electronic books; Electronic books